Adverse Reactions to Drugs of Special Interest in a Pediatric Oncohematology Service - Amaro-Hosey, Kristopher; Danés, Immaculada; Vendrell, Lourdes; Alonso, Laura; Renedo, Berta; Gros, Luis; Vidal, Xavier; Cereza, Gloria; Agustí, Antònia (Frontiers in Pharmacology, 2021)
Introduction: Drugs used in oncological diseases are frequently related to adverse drug reactions (ADRs). Few studies have analyzed the toxicity of cancer treatments in children in real practice. Methods: An observational, longitudinal and prospective study has been carried out in an Oncohematology Service of a tertiary hospital. During 2017, patients exposed to one or more drugs of a previously agreed list were identified and followed- up for at least 6 months each. Characteristics of ADRs, incidence, causality and possible preventability, have been evaluated. Results: 72 patients have been treated with at least one study drug, and 159 ADRs episodes involving at least one of these drugs have been identified, with a total of 293 ADRs. Most episodes required hospital admission (35.2%) or happened during the hospital stay (33%), and 91.2% were severe. Blood disorders were the most frequent ADRs (96; 32.8%), related to thioguanine (42) and pegaspargase (39) mainly, followed by infections (86; 29.4%) related to thioguanine (32), pegaspargase (27), Erwinia asparaginase (14) and rituximab (13). Two ADRs were unknown. Most ADRs were dose-dependent or expectable (>90%). The global incidence of ADR was 3.1/100 days at risk (95% CI 2.7-3.5), with 3.5 ADR/100 days at risk with pegaspargase (95% CI 2.9-4.2), 1.2/100 days at risk with rituximab (95% CI 0.8-1.8) and 11.6/100 days at risk with thioguanine (95% CI 9.4-14.2). Controversial additional measures of prevention, other than those already used, were identified. Conclusions: ADRs are frequent in pediatric oncohematological patients, mainly blood disorders and infectious diseases. Findings regarding incidence and preventability may be useful to compare data between different centers and to evaluate new possibilities for action or prevention.